Photothermal-photocatalytic system and preparation method thereof, hydrogen production equipment and hydrogen fuel cell
By constructing CdS/CoFe2O4p-n heterojunction photocatalyst and combining it with heat-treated carbon foam matrix, the photocorrosion and carrier recombination of CdS photocatalysts are solved, and the photocatalytic hydrogen production efficiency is significantly improved.
Patent Information
- Application Number
- CN202411344864.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing CdS photocatalysts have problems of photocorrosion, rapid carrier recombination and poor cycle stability, which limit their application in photocatalytic hydrogen production.
CdS/CoFe2O4p-n heterojunction photocatalyst was constructed by calcining method and combined with the heat-treated carbon foam matrix to form a photothermal-photocatalytic system.
The photocatalytic hydrogen evolution efficiency is significantly improved, the photocorrosion of CdS is suppressed, the spatial transmission continuity and effective separation of carriers are ensured, and the absorption, conversion and utilization of solar energy is optimized.
Smart Images

Figure CN118846996B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of photocatalytic technology, and in particular to a photothermal-photocatalytic system and a preparation method thereof, as well as a hydrogen production device and a hydrogen fuel cell. Background Art
[0002] The energy crisis and environmental challenges brought about by rapid economic growth have urgently prompted people to seek clean energy and green chemical technology. Among the potential solar fuels, hydrogen energy is a clean energy with high energy density, which may replace traditional fossil fuels as the main energy source in the future.
[0003] As an innovative technology for environmental purification and energy utilization, photocatalysis has great prospects in converting solar energy into storable hydrogen energy. In the past few decades, researchers have focused a lot of attention on material design, and various semiconductor materials, such as metal oxides, metal sulfides, and non-metallic semiconductors, have been explored as photocatalysts for efficient photocatalytic hydrogen production. Among them, n-type semiconductor CdS has attracted widespread attention due to its strong visible light absorption ability and band structure that is conducive to photocatalytic reactions. However, inherent photocorrosion, rapid recombination of carriers, and poor cyclic stability have hindered the application of CdS photocatalysts. Summary of the invention
[0004] In view of this, the purpose of the present application is to provide a photothermal-photocatalytic system and a preparation method thereof, so that the photothermal-photocatalytic system can significantly improve the efficiency of photocatalytic hydrogen evolution;
[0005] Another object of the present application is to provide a hydrogen production device, a hydrogen production method and a hydrogen fuel cell based on the above-mentioned photothermal-photocatalytic system.
[0006] In order to solve the above technical problems / achieve the above purposes or at least partially solve the above technical problems / achieve the above purposes, as the first aspect of the present application, a photothermal-photocatalytic system is provided, comprising a heat-treated carbon foam substrate, and a CdS / CoFe2O4 p-n heterojunction photocatalyst, wherein the pn heterojunction photocatalyst is distributed on the surface of the carbon foam substrate; in the pn heterojunction photocatalyst, CoFe2O4 is loaded on the surface of CdS and a pn heterojunction is formed at the contact point between the two; the mass ratio of CdS and CoFe2O4 is (150-199): (50-1).
[0007] Optionally, the heat treatment is annealing at 100-600° C. for 1-10 h in air; and the carbon foam matrix includes melamine sponge.
[0008] Optionally, the pn heterojunction photocatalyst is obtained by calcining CdS and CoFe2O4 after they are fully contacted.
[0009] Optionally, the surface of the carbon foam matrix further includes polyvinylidene fluoride.
[0010] As a second aspect of the present application, a method for preparing the photothermal-photocatalytic system is provided, comprising:
[0011] CdS / CoFe2O4 p-n heterojunction photocatalyst was prepared using CoFe2O4 and CdS as raw materials;
[0012] The pn heterojunction photocatalyst is mixed evenly with a solvent to obtain a mixed solution, the mixed solution is coated on the surface of a carbon foam substrate, and the photothermal-photocatalytic system is obtained after drying.
[0013] Optionally, the mixed solution further contains polyvinylidene fluoride.
[0014] As a third aspect of the present application, a hydrogen production device is provided, comprising the photothermal-photocatalytic system described in the present application.
[0015] As a fourth aspect of the present application, a hydrogen production method is provided, which uses the photothermal-photocatalytic system described in the present application to contact water, and performs a photocatalytic reaction under light to produce hydrogen.
[0016] As a fifth aspect of the present application, a hydrogen fuel cell is provided, comprising the hydrogen production device described in the present application, wherein the hydrogen produced by the hydrogen production device is converted into electrical energy through an electrochemical reaction as a fuel.
[0017] The present application constructs a CdS / CoFe2O4p-n heterojunction photocatalyst through a calcination process, which can ensure the spatial transmission continuity and effective separation of photogenerated carriers, inhibit the inherent photocorrosion of CdS, and thus significantly improve the photocatalytic efficiency. In addition, the present application combines the CdS / CoFe2O4p-n heterojunction photocatalyst and a carbon foam photothermal material with a wide solar spectrum response range to obtain an efficient photothermal-photocatalytic system, which can convert liquid water into water vapor and decompose water vapor into hydrogen under light irradiation. Compared with the traditional photocatalytic water decomposition hydrogen production system, the photothermal-photocatalytic system described in the present application optimizes the absorption, conversion and utilization of solar energy, increases the overall reaction temperature, and minimizes the gas transport resistance at the catalytic interface, thereby significantly improving the photocatalytic hydrogen production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.
[0019] Figure 1Shown is the morphology structure diagram of the CdS / CoFe2O4p-n heterojunction photocatalyst of the present application;
[0020] Figure 2 Shown is a schematic structural diagram of the photothermal-photocatalytic system of the present application;
[0021] Figure 3 Shown is the morphological structure diagram of the photothermal-photocatalytic system of the present application;
[0022] Figure 4 Shown is the X-ray diffraction (XRD) spectrum of the CdS / CoFe2O4p-n heterojunction photocatalyst of the present application; wherein CCF-1.5 represents the CdS / CoFe2O4p-n heterojunction photocatalyst of the present application;
[0023] Figure 5 The figure shows the test diagram of the CdS / CoFe2O4p-n heterojunction photocatalytic decomposition of water and hydrogen evolution of the present application; wherein CCF-1 / 1.5 / 2 / 3 represent the CdS / CoFe2O4p-n heterojunction photocatalysts of Examples 1-4 of the present application respectively;
[0024] Figure 6 Shown is a photocatalytic hydrogen evolution performance evaluation diagram of the photothermal-photocatalytic system of the present application; wherein, CCF-1.5 / AMS-sink represents the photothermal-photocatalytic system treatment group of the present application completely immersed in water, CCF-1.5 represents the CdS / CoFe2O4p-n heterojunction photocatalyst treatment group of the present application, CCF-1.5 / MS represents the photothermal-photocatalytic system treatment group using non-thermally treated melamine sponge as the matrix, and CCF-1.5 / AMS represents the photothermal-photocatalytic system treatment group of the present application that is not completely immersed in water. DETAILED DESCRIPTION
[0025] The present application discloses a photothermal-photocatalytic system and a preparation method thereof, as well as a hydrogen production device and a hydrogen fuel cell. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. The relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described herein without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0026] It should be noted that, in this document, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or device including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0027] In the first aspect of the present application, in response to the inherent defects of the current CdS photocatalyst, such as photocorrosion, rapid recombination of carriers and poor cyclic stability, the present application changes the traditional complex in-situ synthesis method of heterojunctions and constructs a CdS / CoFe2O4p-n heterojunction photocatalyst through a simple calcination method, which includes CdS and CoFe2O4, wherein the CoFe2O4 is loaded on the surface of CdS, and the CoFe2O4 and CdS form a pn heterojunction at the contact point. In the pn heterojunction catalyst of the present application, the electronic structure at the contact point will change, ensuring the spatial transmission continuity and effective separation of photogenerated carriers, inhibiting the inherent photocorrosion of CdS, thereby changing the activity and selectivity of the catalytic reaction, which is specifically manifested in that the efficiency of photocatalytic hydrogen evolution is significantly improved, which is essentially different from simply mixing two substances, CoFe2O4 and CdS.
[0028] In certain embodiments of the present application, the mass ratio of CdS to CoFe2O4 is (150-199): (50-1), such as 150:50, 180:20, 190:10, 199:1, etc. In other embodiments of the present application, the mass ratio of CdS to CoFe2O4 is (180-199): (20-1), such as 180:20, 190:10, 199:1, etc.; in other embodiments of the present application, the mass ratio of CdS to CoFe2O4 is (190-199): (10-1), such as 190:10, 191:9, 192:8, 193:7, 194:6, 195:5, 196:4, 197:3, 198:2, 199:1, etc.
[0029] In certain embodiments of the present application, the CdS in the pn heterojunction photocatalyst is a nano-scale rod-like structure with a diameter of 30±5nm, the CoFe2O4 is a nano-scale granular structure with a particle size distribution of 1-25nm, and the CoFe2O4 nanoparticles are uniformly dispersed on the surface of the CdS nanorods. Figure 1 .
[0030] In certain embodiments of the present application, the pn heterojunction photocatalyst is obtained by calcining after CdS and CoFe2O4 are fully contacted. The method of fully contacting includes but is not limited to grinding, stirring, ball milling, etc., and the time of full contact is not less than 1 minute, more specifically, it can be 10-60 minutes; the calcination temperature is 150-300°C, and the time is 1-5 hours, for example, the calcination temperature can be 150°C, 180°C, 200°C, 220°C, 250°C, 280°C or 300°C, and the calcination time can be 1 hour, 2 hours, 3 hours, 4 hours or 5 hours. 。
[0031] The research and development of photocatalysts is mostly focused on material design, while efforts to optimize reaction systems are limited. Traditional photocatalytic water splitting is to evenly disperse the photocatalyst in the liquid phase to form a solid-liquid-gas three-phase reaction, which mainly utilizes ultraviolet and visible light in sunlight, ignoring the abundant near-infrared light that accounts for more than 50% of solar energy. Challenges such as poor light absorption, high heat loss, and slow mass transfer in traditional solid-liquid-gas three-phase reactions also hinder the improvement of photocatalytic energy conversion efficiency. Therefore, the present application provides a photothermal-photocatalytic system based on CdS / CoFe2O4p-n heterojunction photocatalyst, including a heat-treated carbon foam substrate and the pn heterojunction photocatalyst described in the present application, wherein the pn heterojunction photocatalyst is distributed on the surface of the carbon foam substrate. The photothermal-photocatalytic system has a carbon foam substrate with a strong photothermal conversion effect. Through the reasonable structural design of the CdS / CoFe2O4p-n heterojunction provided in the application, an interfacial photothermal evaporation catalytic system is formed. This photothermal-photocatalytic solid-supported system optimizes the absorption, conversion and utilization of solar energy, increases the overall reaction temperature, and minimizes the gas transport resistance at the catalytic interface, thereby significantly improving the efficiency of photocatalytic hydrogen production. The schematic diagram of the structure is shown in Figure 2 , SEM morphology structure diagram see Figure 3 .
[0032] In certain embodiments of the present application, the carbon foam matrix includes melamine sponge. In other embodiments of the present application, the melamine sponge is a heat-treated melamine sponge, and compared with the melamine sponge that has not been heat-treated, its photothermal effect has been significantly improved, and the photocatalytic hydrogen evolution rate has been significantly improved. In other embodiments of the present application, the heat treatment is an annealing treatment, more specifically including annealing at 100-600°C in air for 1-10h, for example, the annealing temperature can be selected from 100°C, 200°C, 300°C, 400°C, 420°C, 450°C, 480°C, 500°C or 600°C, and the annealing time can be selected from 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0033] In certain embodiments of the present application, the surface of the carbon foam substrate also includes polyvinylidene fluoride. The introduction of polyvinylidene fluoride can, on the one hand, enable the CdS / CoFe2O4p-n heterojunction catalyst of the present application to be evenly coated on the surface of the carbon foam substrate, thereby preventing the catalyst from falling to the bottom of the carbon foam substrate; on the other hand, it can change the surface of the carbon foam substrate from hydrophilic to hydrophobic, thereby promoting the release of water vapor, preventing the direct contact between the CdS / CoFe2O4p-n heterojunction and liquid water, and accelerating the photocatalytic hydrogen evolution reaction.
[0034] In a second aspect of the present application, a method for preparing the photothermal-photocatalytic system is provided, comprising:
[0035] CdS / CoFe2O4 p-n heterojunction photocatalyst was prepared using CoFe2O4 and CdS as raw materials;
[0036] The pn heterojunction photocatalyst is mixed evenly with a solvent to obtain a mixed solution, the mixed solution is coated on the surface of a carbon foam substrate, and the photothermal-photocatalytic system is obtained after drying.
[0037] In certain embodiments of the present application, the mixed solvent generally adopts an organic solvent, including but not limited to dimethylformamide (DMF), etc. In some other embodiments of the present application, the mixed solution also contains polyvinylidene fluoride, and its concentration can be selected from 1-100 mg / mL, such as 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL. In some other embodiments of the present application, the mass ratio of the pn heterojunction photocatalyst to polyvinylidene fluoride can be selected as 10-100 mg:200-500 mg. For example, the mass of the pn heterojunction photocatalyst can be selected as 10 mg, 20 mg, 30 mg, 40 mg, 50 mg, 60 mg, 70 mg, 80 mg, 90 mg or 100 mg, and the mass of the polyvinylidene fluoride can be selected as 200 mg, 250 mg, 300 mg, 350 mg, 400 mg, 450 mg or 500 mg.
[0038] In a third aspect of the present application, a hydrogen production device is provided, comprising the photocatalytic system described in the present application. The hydrogen production device may also include a hydrogen storage device to store hydrogen generated by photocatalysis.
[0039] In the fourth aspect of the present application, when the photothermal-photocatalytic system described in the present application is used to produce hydrogen, the photothermal-photocatalytic system is contacted with water, and a photocatalytic reaction is carried out under light to produce hydrogen; wherein the surface of the carbon foam substrate of the photothermal-photocatalytic system coated with a pn heterojunction photocatalyst is not lower than the water surface, which is more conducive to hydrogen evolution efficiency.
[0040] In the fifth aspect of the present application, a hydrogen fuel cell is provided, including the hydrogen production device described in the present application, wherein the hydrogen produced by the hydrogen production device is converted into electrical energy through an electrochemical reaction as a fuel to drive the operation of energy-consuming equipment. The produced hydrogen is input into the fuel cell, and the electrons of the hydrogen atoms are blocked by the proton exchange membrane in the battery, and are conducted from the negative electrode to the positive electrode through an external circuit to become electrical energy to drive the motor; however, the protons can be combined with oxygen through the proton exchange membrane to form pure water mist and discharged, which effectively reduces the air pollution problem caused by other fuel vehicles. The energy-consuming equipment includes but is not limited to electric vehicles, electric vehicles, balance vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.
[0041] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0042] The following is a further description of a photothermal-photocatalytic system and its preparation method, as well as a hydrogen production device and a hydrogen fuel cell provided in the present application.
[0043] Embodiment 1:
[0044] S1. Put 198 mg of CdS nanorods and 2 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0045] S2. Cut a large piece of commercial melamine sponge into required sizes and anneal it in a muffle furnace at 450 °C for 3 h at a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0046] S3, 20 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 20 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0047] Embodiment 2:
[0048] S1. Put 197 mg of CdS nanorods and 3 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0049] S2. Cut a large piece of commercial melamine sponge into required sizes and anneal it in a muffle furnace at 450 °C for 1 h at a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0050] S3, 20 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 20 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0051] Embodiment 3:
[0052] S1. Put 196 mg of CdS nanorods and 4 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0053] S2. Cut a large piece of commercial melamine sponge into required sizes and anneal it in a muffle furnace at 600 °C for 1 h at a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0054] S3, 20 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 20 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0055] Embodiment 4:
[0056] S1. Put 194 mg of CdS nanorods and 6 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0057] S2. Cut a large piece of commercial melamine sponge into required sizes and anneal it in a muffle furnace at 100 °C for 10 h with a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0058] S3, 20 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 20 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0059] Embodiment 5:
[0060] S1. Put 197 mg of CdS nanorods and 3 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0061] S2. Cut a large piece of commercial melamine sponge into required sizes and anneal it in a muffle furnace at 450 °C for 1 h at a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0062] S3. 30 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 30 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4 p-n heterojunction.
[0063] Embodiment 6:
[0064] S1. Put 197 mg of CdS nanorods and 3 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0065] S2. Cut a large piece of commercial melamine sponge into required sizes and anneal it in a muffle furnace at 450 °C for 5 h with a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0066] S3. 40 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 30 min. Subsequently, the obtained mixed solution was evenly drop-coated on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4 p-n heterojunction.
[0067] Embodiment 7:
[0068] S1. Put 197 mg of CdS nanorods and 3 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0069] S2. Cut a large piece of commercial melamine sponge into required sizes and anneal it in a muffle furnace at 450 °C for 1 h at a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0070] S3. Disperse 50 mg of CdS / CoFe2O4 composite photocatalyst in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasound for 40 min. Then, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0071] Embodiment 8:
[0072] S1. Put 197 mg of CdS nanorods and 3 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0073] S2. Cut a large piece of commercial melamine sponge into the required size and anneal it in a muffle furnace at 450 °C for 1 h with a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0074] S3. 60 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 40 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0075] Embodiment 9:
[0076] S1. Put 199 mg of CdS nanorods and 1 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0077] S2. Cut a large piece of commercial melamine sponge into the required size and anneal it in a muffle furnace at 450 °C for 1 h with a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0078] S3, 20 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 20 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0079] Embodiment 10:
[0080] S1. Put 150 mg of CdS nanorods and 50 mg of CoFe2O4 nanoparticles into an agate mortar, add 1 ml of anhydrous ethanol, grind for 30 min, collect the complex into a corundum magnetic boat, and then transfer the corundum magnetic boat to a muffle furnace for calcination. After calcination at 220 °C for 2 h, the CdS / CoFe2O4 p-n heterojunction catalyst was obtained.
[0081] S2. Cut a large piece of commercial melamine sponge into the required size and anneal it in a muffle furnace at 450 °C for 1 h with a heating rate of 10 °C / min. After cooling to room temperature, a carbon foam photothermal material was obtained.
[0082] S3, 20 mg of CdS / CoFe2O4 composite photocatalyst was dispersed in 5 mL of dimethylformamide solution containing polyvinylidene fluoride (50 mg / mL) by ultrasonication for 20 min. Subsequently, the obtained mixed solution was evenly dripped on the surface of carbon foam with a pipette. Finally, the obtained composite material was dried in a vacuum oven at 80 °C for 12 h to obtain an interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction.
[0083] Experimental example:
[0084] (1) The morphology and structure of the CdS / CoFe2O4 p-n heterojunction prepared in Example 2 of the present application are as follows: Figure 1As shown in: Figures a and b are the TEM and HRTEM images of the prepared CdS / CoFe2O4p-n heterojunction, respectively. The average diameter of the CdS nanorods is about 30 nm, and the CoFe2O4 nanoparticles are uniformly dispersed on the surface of the CdS nanorods, indicating the successful construction of the CdS / CoFe2O4p-n heterojunction. In addition, the microstructure of the prepared samples was further studied by high-resolution transmission electron microscopy (HRTEM). The lattice spacings of 0.253 nm and 0.329 nm in Figure b are attributed to the (311) plane of CoFe2O4 and the (104) plane of CdS, respectively. The lattice fringes of CdS in CdS / CoFe2O4 are the same as those of pure CdS, indicating that the loading of CoFe2O4 does not change the original structure of CdS. The X-ray diffraction (XRD) patterns of the prepared CdS, CoFe2O4 and CdS / CoFe2O4 are shown in Figure 2. Figure 3 As shown. For the XRD spectrum of pure CoFe2O4, the main diffraction peak matches the diffraction peak of spinel CoFe2O4 (JCPDS No.22-1086). When CoFe2O4 is compounded with CdS, the diffraction peak of CdS / CoFe2O4 is similar to that of pure CdS, which is attributed to the low content of CoFe2O4 in the composite, and also shows that the loading of CoFe2O4 has no effect on the crystal structure of CdS. The morphological characteristics and XRD characteristics of the CdS / CoFe2O4 p-n heterojunction prepared in other embodiments are basically consistent with the results shown in Example 2.
[0085] (2) The photocatalytic water decomposition and hydrogen evolution performance of the CdS / CoFe2O4 p-n heterojunction prepared in Examples 1-4 of the present application is tested as follows: Figure 5 As shown, the further composite of CdS and CoFe2O4 exhibits a higher hydrogen evolution rate compared to pure CdS. The maximum hydrogen evolution rate of CdS / CoFe2O4 nanocomposite is 76.5 µmol / h, which is 4.9 times that of pure CdS. The CdS / CoFe2O4 p-n heterojunction photocatalyst ensures the spatial transmission continuity and effective separation of photogenerated carriers.
[0086] (3) Figure 3a and 3b are SEM images of the carbon foam prepared in Example 7 of the present application and the interfacial photothermal evaporation catalytic system based on the CdS / CoFe2O4p-n heterojunction, respectively. The carbon foam is a three-dimensional porous structure with uniform pores. The highly porous structure and excellent hydrophilicity of the carbon foam ensure that water can be quickly transferred in the carbon foam. A mixed solution containing polyvinylidene fluoride and a photocatalyst is coated on the surface of the carbon foam to construct an interfacial photothermal evaporation catalytic system based on the CdS / CoFe2O4p-n heterojunction. The SEM image shows that the CdS / CoFe2O4p-n heterojunction photocatalyst is uniformly coated on the porous framework of the carbon foam. The morphological characteristics of the photocatalytic systems prepared in other embodiments are basically consistent with the results shown in Example 7.
[0087] (4) The photocatalytic decomposition and hydrogen evolution performance of the interfacial photothermal evaporation catalytic system based on CdS / CoFe2O4p-n heterojunction prepared in Example 7 of the present application is evaluated as follows: Figure 6 As shown, its optimal photocatalytic hydrogen evolution rate is 254.1 µmol / h, which is 3.3 times that of the CdS / CoFe2O4 three-phase powder system. When the surface of the photocatalytic system of the present application is completely immersed in water, its hydrogen evolution rate is poor, only 14.2 µmol / h. This is mainly because it is more difficult for hydrogen bubbles to desorb in the liquid phase system. Therefore, during actual hydrogen production, the surface coated with the photocatalyst cannot be lower than the water surface to avoid affecting the hydrogen production rate. In addition, compared with the heat-treated commercial melamine substrate, when the commercial melamine sponge is directly used as the substrate, the hydrogen evolution rate is only 114.5 µmol / h. This is due to the poor photothermal effect of the unheat-treated commercial melamine sponge.
[0088] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A photothermal-photocatalytic system, characterized in that: The invention comprises a CdS / CoFe2O4 p-n heterojunction photocatalyst, polyvinylidene fluoride and a heat-treated melamine sponge, wherein the pn heterojunction photocatalyst and the polyvinylidene fluoride are distributed on the surface of the melamine sponge; in the pn heterojunction photocatalyst, CoFe2O4 is loaded on the surface of CdS and a pn heterojunction is formed at the contact point between the two, and the pn heterojunction photocatalyst is obtained by calcining after the CdS and CoFe2O4 are fully contacted; and the mass ratio of the CdS and CoFe2O4 is 180-199: 20-1.
2. The photothermal-photocatalytic system according to claim 1, characterized in that: The heat treatment is annealing at 100-600° C. for 1-10 h in air.
3. The method for preparing the photothermal-photocatalytic system according to claim 1, characterized in that: include: CdS / CoFe2O4 pn heterojunction photocatalyst was prepared using CoFe2O4 and CdS as raw materials; The pn heterojunction photocatalyst, polyvinylidene fluoride and solvent are uniformly mixed to obtain a mixed solution, the mixed solution is coated on the surface of the heat-treated melamine sponge, and the photothermal-photocatalytic system is obtained after drying.
4. A hydrogen production device, characterized in that: A photothermal-photocatalytic system comprising any one of claims 1-2.
5. A method for producing hydrogen, characterized in that: The photothermal-photocatalytic system according to any one of claims 1 to 2 is brought into contact with water to carry out a photocatalytic reaction under light to produce hydrogen; wherein the surface of the melamine sponge coated with a pn heterojunction photocatalyst in the photothermal-photocatalytic system is not lower than the water surface.
6. A hydrogen fuel cell, characterized in that: It comprises the hydrogen production equipment as described in claim 4, wherein the hydrogen produced by the hydrogen production equipment is used as fuel and converted into electrical energy through electrochemical reaction.
Citation Information
Patent Citations
All-solid-state heterostructure catalyst material as well as preparation method and application thereof
CN114713262A